IGF1-Stimulated Posttraumatic Hippocampal Remodeling Is Not Dependent on mTOR - Littlejohn, Erica L.; DeSana, Anthony J.; Williams, Hannah C.; Chapman, Rudy T.; Joseph, Binoy; Juras, Jelena A.; Saatman, Kathryn E. (Frontiers in Cell and Developmental Biology, 2021)
However, many hippocampal neurons born after injury develop abnormally, and the number that survive long-term is debated. In experimental TBI, insulin-like growth factor-1 (IGF1) promotes hippocampal neuronal differentiation, improves immature neuron dendritic arbor morphology, increases long-term survival of neurons born after TBI, and improves cognitive function. One potential downstream mediator of the neurogenic effects of IGF1 is the mammalian target of rapamycin (mTOR), which regulates proliferation as well as axonal and dendritic growth in the CNS. Excessive mTOR activation is posited to contribute to aberrant plasticity related to posttraumatic epilepsy, spurring preclinical studies of mTOR inhibitors as therapeutics for TBI. The degree to which pro-neurogenic effects of IGF1 depend upon the upregulation of mTOR activity is currently unknown. Using phosphorylated S6 immunostaining, we show that controlled cortical impact TBI triggers mTOR activation in the dentate gyrus in a time-, region- and injury severity-dependent manner. Posttraumatic mTOR activation was amplified in mice with astrocytic conditional overexpression of IGF1. To determine whether mTOR activation is necessary for IGF1-mediated stimulation of posttraumatic hippocampal neurogenesis, wildtype and IGF1 transgenic mice received the mTOR inhibitor rapamycin daily beginning at 3 days after TBI, following pulse labeling with bromodeoxyuridine. In wild-type mice, rapamycin administration decreased dendritic growth of immature neurons without affecting numbers of newborn neurons surviving to 10 days post-injury. Surprisingly, in mice with IGF1 overexpression, delayed mTOR inhibition significantly increased the density of posttrauma-born hippocampal neurons. Further, IGF1 transgenic mice were completely resistant to rapamycin-mediated impairment of dendritic development. These data suggest that the interplay between IGF1 and mTOR signaling is distinct for individual stages of posttraumatic neurogenesis including neuronal differentiation and dendritic growth. Because beneficial effects of IGF1 on hippocampal neurogenesis were maintained or even enhanced with inhibition of mTOR, combination therapy approaches may hold promise for TBI.